Spectrum of epilepsy – prevalence, impact, and treatment gap: an epidemiological study from Al-Quseir, Egypt - El tallawy H; Farghaly W; Rageh T; Shehata G; Metwally N; Badry R; Sayed M; Abdelwarith A; Kandil M; Ibrahim MAAEH; Mohamed K; Tohamy A (Neuropsychiatric Disease and Treatment)
Hamdy N El-Tallawy,1 Wafaa M Farghaly,1 Tarek A Rageh,1 Ghaydaa A Shehata,1 Nabil A Metwally,2 Reda Badry,1 Mohammed A Sayed,3 Ahmed M Abdelwarith,2 Mahmoud R Kandil,1 Mohamed A Hamed,1 Khaled O Mohamed,1 Amal M Tohamy11Department of Neurology, Assiut University, Assiut, 2Department of Neurology, Faculty of Medicine, Al-Azhar University – Assiut Branch, Assiut, 3Department of Neurology, Sohag University, Sohag, EgyptBackground: Epidemiology continues to be an important research tool in the study of epilepsy and related disorders, providing a better understanding of the frequency, causes, and natural history of the disorder.Objective: To estimate the prevalence of epilepsy in Al-Quseir, Red Sea Governorate, Egypt, and its magnitude of treatment gap.Methods: The study was part of a door-to-door study, including every door, to screen all inhabitants in Al-Quseir (33,818 inhabitants) by three specialists of neurology and 15 female social workers (for demographic data collection) using a standardized screening questionnaire. All suspected cases were subjected to detailed history, clinical examination, and electroencephalogram. Neuroimaging studies and estimation of serum drug level were done in select cases if needed.Results: The study revealed that the lifetime prevalence rate of epilepsy in Al-Quseir is 5.5/1,000, with the highest peak during early childhood, while that of active epilepsy is 3.3/1,000 population. The annual incidence rate is 48/100,000, and the age-specific incidence rate has a U-shaped pattern with two peaks of incidence in early infancy and elderly life. Localization-related epilepsy is the most frequently encountered type (58.8%). The treatment gap of epilepsy in Al-Quseir is 83.8%.Conclusion: The lifetime prevalence of epilepsy in Al-Quseir city, Red Sea Governorate, was 5.5/1000. Keywords: epidemiology, epilepsy, treatment gap, Egypt, Al-Quseir, epidemiology